Compliance Of Dental Staff And Students To Dental Guidelineamidst The Covid-19 Pandemic: An Institutional Analysis - Nor Azura Ahmad Tarmidzi; Diana Md Zahid; Nor Haliza Binti Mat Baharin; Muhammad Syafiq Bin Alauddin (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 02-2021) [June 2021]